Deformation and failure behaviour of 316 LN austenitic stainless steel weld joint under thermomechanical low cycle fatigue in as-welded and thermally aged conditions. (August 2021) - Suresh Kumar, T.; Nagesha, A.; Mariappan, K.; Kumar Dash, Manmath
Highlights: Prior thermal ageing increased the TMF life of 316 LN SS weld joint. Dynamic strain ageing and creep are more pronounced in as-welded condition. The failure location gets shifted to the weld region following thermal ageing. Interaction among the DSA, creep and microstructural changes contributed to failure. Abstract: Beneficial influence of prior thermal ageing on the cyclic life was demonstrated on a type 316 LN austenitic stainless steel weld joint under thermomechanical fatigue. Tests performed using different temperature intervals showed that the crack initiation occurs mostly in the heat affected zone in the as-welded joint. However, the failure location gets shifted to the weld region following thermal ageing. Mechanisms governing life variations between the as-welded and aged joints were identified. The localization of plastic deformation in different regions of the joints and its dependence on the microstructure was evaluated and explained on the basis of detailed EBSD investigations.